New species of Polysphondylium from Madagascar. (1st January 2016) - Cavender, James C.; Landolt, John C.; Romeralo, Maria; Perrigo, Allison; Vadell, Eduardo M.; Stephenson, Steven L.
Abstract : Two series of samples collected for isolation of dictyostelid cellular slime molds (dictyostelids) in Madagascar yielded a relatively large number of isolates of Polysphondylium . Most of these turned out to be species new to science that show varying degrees of clustering from unclustered to coremiform as well as an ability to migrate. Migratory ability (phototaxis) is a common feature of species assigned to Group 2 of the Polysphondylia and is common in the new species from Madagascar. Another common feature, clustering, appears to be a strategy for keeping fruiting bodies erect for a longer time in a climate that is relatively dry, whereas migratory ability may function seasonally when there is more rainfall. Thirteen species are described herein. Each of these is characterized by a particular set of distinguishing features, and collectively they expand our concept of the genus Polysphondylium .